The authorship in nursing literature: an against trend? Authorship in nursing literature - Vitale, Elsa; Moretti, Lorenzo; Notarnicola, Angela; Di Dio, Francesca; Rifino, Francesco; Moretti, Biagio (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim of the work: Women graduated and engaged in the scientific world are in increasing numbers. The present study aimed to analyze the gender difference in nursing scientific publication and to understand the trend in nursing science is the same or different to that reported in other scientific disciplines. Methods: We considered the first name in the authorship of the highest impacted factor journals related of year 2019 in the Web of Science database for the period 2015-2019, as: the International Journal of Nursing Studies (IJNS) and the Nursing Outlook (NO). Considering the proposed economic classification of the “World bank”, weassessed the gender of the first authors searched with the relative degree of wealth of their countries thanks to the chi square test. Results: From 1st January 2015 to 31st December 2019 a total of 1171 first authors were identified. Of these, 776 (66.27%) belonged to the IJNS and 395 (33.73%) to the NO. The female gender was most representative than the male gender into two journals. In fact, 982 (83.9%) citations belong to female researchers while 189 (16.1%) citations belong to male researchers. However, the same trend is not evaluated in the Italian scenario where the male gender predominates over the female one in scientific production. Conclusions: Nursing scientific production shows a counter trend compared to other scientific disciplines, highlighting a predominance of the female sex over the male one. This difference is more pronounced in the more economically developed countries.